2019
DOI: 10.1093/femsle/fnz008
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity, lifestyles and evolutionary origins of DPANN archaea

Abstract: Archaea—a primary domain of life besides Bacteria—have for a long time been regarded as peculiar organisms that play marginal roles in biogeochemical cycles. However, this picture changed with the discovery of a large diversity of archaea in non-extreme environments enabled by the use of cultivation-independent methods. These approaches have allowed the reconstruction of genomes of uncultivated microorganisms and revealed that archaea are diverse and broadly distributed in the biosphere and seemingly include a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
183
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(219 citation statements)
references
References 110 publications
14
183
4
Order By: Relevance
“…the Methanonatronoarchaeia (20,21) or Candidate Divison MSBL1, thought to encompass methanogens (22) and/or sugar-fermentors (23), but also other archaeal groups not specifically associated with salty systems. These included Thermoplasmata and Archaeoglobi within 45 Euryarchaeota, Woesearchaeota and other lineages (Aenigmarchaeota, Altiarchaeales) usually grouped as DPANN (24)(25)(26) and Thaumarchaeota and Crenarchaeota (Sulfolobales) within the TACK/Proteoarchaeota (27) ( Fig. 3a; Supplementary Data S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the Methanonatronoarchaeia (20,21) or Candidate Divison MSBL1, thought to encompass methanogens (22) and/or sugar-fermentors (23), but also other archaeal groups not specifically associated with salty systems. These included Thermoplasmata and Archaeoglobi within 45 Euryarchaeota, Woesearchaeota and other lineages (Aenigmarchaeota, Altiarchaeales) usually grouped as DPANN (24)(25)(26) and Thaumarchaeota and Crenarchaeota (Sulfolobales) within the TACK/Proteoarchaeota (27) ( Fig. 3a; Supplementary Data S2).…”
Section: Resultsmentioning
confidence: 99%
“…3c, red dots) failed to amplify Nanohaloarchaeota and other divergent DPANN lineages. These likely encompass ectosymbionts/parasites (24)(25)(26)28). Given their relative abundance and co-occurrence in these and other ecosystems, it is tempting to hypothesize that Nanohaloarchaeota are (ecto)symbionts of Halobacteria; likewise, Woesearchaeota might potentially be associated with Thermoplasma-like archaea.…”
Section: Resultsmentioning
confidence: 99%
“…Halophilic fermentative bacteria are known to play a role in chitin mineralization in hypersaline habitats worldwide 5-7 , and more recently it was shown that haloarchaea also take part in the primary degradation of polymeric organic matter in many of the same habitats 8-11 . Here we reveal the role of haloarchaea as chitinotrophic hosts for nanohaloarchaea, the extremely halophilic members of the DPANN superphylum 12-15 .…”
Section: Introductionmentioning
confidence: 96%
“…The DPANN radiation 12 , named after the first members of this group (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota) 11 , comprises one of these recently proposed archaeal clades and is now thought to be comprised of at least ten and (according to NCBI taxonomy) putative phylum-level lineages 13,14 . Most members of the DPANN archaea are characterized by small cell sizes and reduced genomes, which code for a limited set of metabolic proteins 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, analyses focusing on the placement of selected DPANN lineages in isolation, such as Nanoarchaeota and Parvarchaeota, relative to other Archaea, have led to the conclusion that these represent fast-evolving Euryarchaeota 28,29 . Furthermore, it is debated whether the free-living Altiarchaeota belong to the DPANN radiation, form an independent lineage or belong to Euryarchaeota 8,9,14,30,31 . A potential cause for these conflicting topologies is that DPANN are often found on long branches in phylogenetic trees; these long branches might result from compositional biases or fast evolutionary rates 32,33 (as seen for obligate bacterial endosymbionts 34,35 ) or might reflect genomic under sampling of the true diversity of this group 9 .…”
Section: Introductionmentioning
confidence: 99%